Thiocyanate: a review and evaluation of the kinetics and the modes of action for thyroid hormone perturbations. (9th August 2017) - Willemin, Marie-Emilie; Lumen, Annie
Abstract: Exposure of the population to thiocyanate is predominantly through the diet and cigarette smoke. Thiocyanate is a potential thyroid disruptor due to its capacity to inhibit the uptake of iodide by the thyroid. Thiocyanate also interacts with the enzymatic reactions associated with iodide organification and thyroid hormone synthesis. Quantification of the dose–response relationships of thiocyanate and alteration in thyroid hormone levels is important for evaluating the risk of exposure to thiocyanate in humans. In this review, we highlight the key whole-body and intra-thyroidal aspects of thiocyanate kinetics in rats and its various modes of action for perturbing thyroid function. The inter-play between the various transporter- and enzyme-mediated modes of action contributes to the complexity in the dose–response relationship determinations for thiocyanate. We map the available modes of action in a mechanistic and quantitative manner. Findings summarized in this study can help support the development of a quantitative model to study the interaction effects of thiocyanate on the thyroid function. Additionally, the data gaps identified can help guide future experimental designs to characterize further thiocyanate dose–response. Finally, the strengths and weaknesses in current risk assessment considerations used for thiocyanate as a component of thyroid-active chemical mixtures are discussed.